UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI PERSIAPAN KEMERDEKAAN MELALUI METODE BERMAIN PERAN PADA KELAS V SDN 1 TEMPUREJO - Ridho Afriyanto; Sungeng Eko Putro Widoyoko; Nur Ngazizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
A research entitled "Efforts to Improve Student Learning Outcomes in Independence Preparation Material Through Role Play Method in Class V of SDN 1 Tempurejo" has been conducted. Elementary School Teacher Education, FKIP, Muhammadiyah University of Purworejo. This study aims to improve learning outcomes in the independence preparation science material through the role play method of class V of SDN 1 Tempurejo. The design of this research is classroom action research (PTK) with two cycles. The subjects in this study were class V students of SDN 1 Tempurejo, with a total of 18 students. The data collection technique used interviews, observations, and tests. Data analysis used descriptive analysis. The results of the study were: (1) Pre-cycle it can be seen that the level of learning completeness of students classically only reached 16.6% with a total of 3 students completing the lesson while the number of students who had not completed it was 15 students (83.4%). With an average of 48.05. In the pre-cycle, data was obtained using document analysis techniques. (2) In cycle I, 9 students completed (50%) and 9 students did not complete (50%). With an average of 58.05. With a success indicator of ≥70, it is still necessary to conduct cycle II (3) In cycle II, the number of students who completed was 17 students (94.4%) and only 1 student did not complete (5.6%), and an average of 76.05. Thus, the role playing method can improve the learning outcomes of class V students at SDN 1 Tempurejo.